Co-teaching the solution to the ‘Continuum of Support’ and supporting positive behaviour. Or is it that simple? A Case Study - Dalton, Patricia (Trinity College (Dublin, Ireland). School of Education, 2021)
Inclusive education is the goal of the Irish education system; its aim is for all students to have the opportunity to be educated with their peers. Over time, this has been driven by a change in governmental policy and provision. One of these provisions is to free up teacher allocation to support the emerging needs of the students. Co-teaching is viewed as a best practice approach to supporting all students in the ‘Continuum of Support’ (DES, 2007, p19). The case study investigates the use of co-teaching in a mainstream, co-education secondary school (the School). A mixed-methods approach was used to gain an insight into the experiences and reflections of teachers working in co-teaching partnerships within the School. The findings of the case study were established from the researcher conducting five semi-formal interviews with teachers working in a co-teaching partnership and a whole school teaching body questionnaire with 35 respondents. The research findings indicate that there is a positive benefit of co-teaching to the School community. The research indicates that this is the result of students having more access to teachers for help and support. There is more focus by the students on task activity, thereby reducing the effect of negative behaviour on teaching and learning within the classroom. The researcher found that where there is a lack of parity within the co-teaching relationships, it impeded the full benefit of the co-teaching experience for both students and teachers alike. As a result of the impact of the Covid-19 pandemic and its effect on Irish society as a whole, the researcher was required to make adaptations to the proposed data collection methods. An online questionnaire acted as an alternative to classroom-based observations and instead of conducting semi-formal interviews in person they were conducted on an online video conference platform ‘Microsoft Teams’. The findings of the case study established the need for co-teaching relationships to have time to form and develop. Whilst there is a benefit to reducing the student-teacher ratio, co-teaching can also bring much more colour and understanding of the subject being taught. It was clear from the research that while there was a willingness from the parties involved for this to happen, it was often impeded by a lack of planning time within the system.
Keywords: Positive Behaviour Management; Education